2014
DOI: 10.3390/s140813476
|View full text |Cite
|
Sign up to set email alerts
|

From the Solution Processing of Hydrophilic Molecules to Polymer-Phthalocyanine Hybrid Materials for Ammonia Sensing in High Humidity Atmospheres

Abstract: We have prepared different hybrid polymer-phthalocyanine materials by solution processing, starting from two sulfonated phthalocyanines, s-CoPc and CuTsPc, and polyvinylpyrrolidone (PVP), polyethylene glycol (PEG), poly(acrylic acid-co-acrylamide) (PAA-AM), poly(diallyldimethylammonium chloride) (PDDA) and polyaniline (PANI) as polymers. We also studied the response to ammonia (NH3) of resistors prepared from these sensing materials. The solvent casted films, prepared from s-CoPc and PVP, PEG and PAA-AM, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
2
19
1
Order By: Relevance
“…PCo1 ‐ PCo5 supramolecular structure change comparable to P1 is connected with the catalyst use in the polymer synthesis. It was previously reported that the use of phthalocyanines leads to a decrease in particle size and an increase in the homogeneity of the supramolecular structure of polyaniline, which is also observed for the studied samples.…”
Section: Resultssupporting
confidence: 76%
“…PCo1 ‐ PCo5 supramolecular structure change comparable to P1 is connected with the catalyst use in the polymer synthesis. It was previously reported that the use of phthalocyanines leads to a decrease in particle size and an increase in the homogeneity of the supramolecular structure of polyaniline, which is also observed for the studied samples.…”
Section: Resultssupporting
confidence: 76%
“…DMBz is the best MSDI developed in the laboratory. [16,26] Its sensitivity was of the same order of magnitude as the polymer-based devices [27][28][29][30][31] but lower than devices made from graphene [32] for which desorption is obtained by heating at ca. 200°C, or from hybrid materials, e.g.…”
Section: Comparative Overviewmentioning
confidence: 91%
“…Using DFT calculations and spectral investigation, it has been shown that ammonia and amines interacts with the central metal ion inside the phthalocyanine ring and pr eferably forms a five-coordinated complex with MPcs with charge transfer to phthalocyanine molecule [49][50][51][52]. The electron charge transfers from electron donor NH 3 molecule to MPc resulting in a decrease of the holes density, hence causing a marked increase in the film's resistance [53].…”
Section: Comparative Study Of the Sensor Properties Of Cupc Filmsmentioning
confidence: 99%